SOFTWARE QUALITY AND CERTIFICATION: PERCEPTION AND PRACTICES IN MALAYSIA (Journal of Information and Communication Technology, 2006)
Recently, there has been an increasing amount of literature on software quality and at the same time complaints are reported widely on the quality status of software products. In the past few years we see a tremendous growth of companies and agencies involve in software industries not only in Malaysia but also in the entire world. The emergence of Multimedia Super Corridor (MSC) in Malaysia in 1996 was the starting point for the blooming of software and ICT related companies. Despite that, not much attention is given to the quality of the software product that is being developed by various categories of companies. The companies could not justify the quality of their products to the users and users are left with uncertainties on the quality of the software. A study was conducted to investigate the current practice and perception on software quality and assessment in Malaysian industries. Forty-three organisations were surveyed to answer several issues on quality and certification. Some of the important findings from this survey are the need for standard and mechanism in software assessment and the need for independent party certification to justify the quality status of software products. This paper discusses more finding of this survey.